2017
DOI: 10.1111/1750-3841.13641
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Volatile Composition Changes of Cooked Sausages Stuffed in a New Casing Formulation Based in Surfactants and Lactic Acid During Long‐Term Storage

Abstract: The objective of this research was to investigate the effects of different modified casings and storage time on the quality attributes of cooked sausages using principal component analysis (PCA) and discriminant analysis. The effects of modifying different casing treatments on sausages' color (L , a , b ), pH, and texture (hardness, springiness, cohesion, gumminess, chewiness) after 36-d storage were estimated by PCA. According to the PCA, lightness at day 36 was correlated to sample stuffed in casing with tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Sausages contain coarse pieces of fat, salted meat, spices and seasoning, encased in natural or artificial casings (Mendonca, ). As grinding or chopping is involved in sausage production, sausages are susceptible to microorganism contamination and oxidation (Mendonca, ; Feng et al ., , ,b; Feng & Sun, ; Feng & Li, ; Feng et al, ). Numerous efforts have been made to prolong the shelf life of sausages by means of either physical treatments (Feng et al ., ) or adding chemical reagents (Kurćubić et al ., ) as well as improving packaging (Pereira et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Sausages contain coarse pieces of fat, salted meat, spices and seasoning, encased in natural or artificial casings (Mendonca, ). As grinding or chopping is involved in sausage production, sausages are susceptible to microorganism contamination and oxidation (Mendonca, ; Feng et al ., , ,b; Feng & Sun, ; Feng & Li, ; Feng et al, ). Numerous efforts have been made to prolong the shelf life of sausages by means of either physical treatments (Feng et al ., ) or adding chemical reagents (Kurćubić et al ., ) as well as improving packaging (Pereira et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…No clear pattern was shown for chewiness and springiness, but the hardness parameter in all formulations increased during storage time, while cohesiveness slightly decreased (Table ). Increases in hardness during storage of sausages is associated with water loss (Capitani et al., ; Feng et al., ; Fernández‐Ginés et al., ; Pintado et al., ; Ruiz‐Capillas et al., ). At the end of the shelf‐life study, FCP and control formulations showed similar hardness values, whereas lower values were detected in CCP formulation.…”
Section: Resultsmentioning
confidence: 99%
“…After image acquisition, 5 g of sample was aseptically collected from the sausage slice and homogenized with 45 mL distilled water for 1 min, as described by Zdolec and others () and Feng and others (). pH values were measured using a digital pH‐meter (Module‐C, Sevenexcellence Instr., Switzerland) in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the meat processing techniques for cooling (Feng and others , , , , , , ; Feng and Sun ; Feng and Li ), drying (Başlar and others ), and packaging (Saenmuang and others ) to enhance the products’ quality, rapid and reliable detection methods are also highly desirable for the fast‐paced production in the processing environment (Kamruzzaman and others ). Hyperspectral imaging (HSI), as an innovative technology, can simultaneously obtain both spatial and spectral information from a sample (Kamruzzaman and others ; Feng and others ).…”
Section: Introductionmentioning
confidence: 99%